Mobilising our skills and values for the data centric world of artificial intelligence - Cox, Andrew (Journal of EAHIL, 2024)
Because current conceptualisations of how to achieve Artificial Intelligence are data driven, so information professional skills applied to data become highly relevant. Translating our well established information skills to the context of data management and stewardship could be invaluable in such areas as data search, understanding data provenance, copyright issues, promoting data sharing and standards based description of data, data disposition or preservation, data ethics, and in promoting data literacy. As a profession we have a valuable and unique contribution to make through information skills applied to data, but we need to include data more in our vocabulary and thinking.